Towards holistic environmental policy assessment. multi-criteria frameworks and recommendations for modelers - Oxana Soimu; Cruz E. Borges; Leandro M. Ferrón; Aitziber Mugarra (npj Climate Action)
Abstract The context of the triple transition requires moving beyond traditional policymaking toward a multidimensional and integrated approach. This study explores the development of a multi-criteria framework to better align policy design with societal needs and planetary boundaries. The research identifies key dimensions spanning economic, social, environmental, and cultural domains essential for effective policy formulation. Using this framework, the study assesses the extent to which a number of Integrated Assessment Models (IAMs) incorporate these dimensions. Findings reveal absence of some of the dimensions in IAMs, particularly in areas prioritized by experts and society, such as education, health, and access to clean water and sanitation. The results highlight the need for more inclusive and holistic modelling tools to guide sustainable policymaking in the face of ongoing global context.